PROTOTYPES, MEANINGS AND MOTION: COGNITIVE EVOLUTION OF SPANISH ACOSTARSE - Fernandez Jaen, Jorge (International Journal of English Studies, 2009)
The aim of this paper is to analyse the Spanish verb acostarse, following the theoretical tools established by Geeraerts (1997). From the perspective of Cognitive Semantics, linguistic categories evolve from prototypic to new meanings as a result of metonymic or metaphorical projections along the history of a language. In this way, I will study the evolution of the verb acostarse, from its latin meaning of rib (which generates a directional prototype) to its current polisemy, in which the meaning of to lie down prevails.